Compositional variability of the aerosols collected in Sfax (Central Tunisia). (July 2018) - Saad, Mohamed; Bibi, Meriam; Masmoudi, Mohamed; Chevaillier, Servanne; Alfaro, Stephane C.
Abstract: In order to assess the variability of the chemical composition of atmospheric aerosols in Central Tunisia and determine their origin, 140 aerosols samples were collected from March 2015 to April 2016 in the industrial city of Sfax. The particles collected on membranes were submitted to X-ray Fluorescence analysis and the concentrations of sixteen elements (Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, Mn, Fe, Ni, Cu, Zn and Pb) quantified. According to the values of their enrichment factors (EF) relative to the composition of the Earth crust and of sea-salt, these elements can be classified in three main categories: 1) crustal (Al, Si, Fe, Ca, Ti, Ni, P, and Mn), 2) marine (Na, Cl), and 3) anthropogenic (S, Zn, Cu, and Pb). Then, we apply the Positive Matrix Factorization (PMF) to the dataset in order to assess the profiles and contributions of the main sources of the aerosol. Beside the marine and anthropogenic factors, 3 other factors are necessary to represent the mineral dust component, which emphasizes the diversity of its sources. In usual conditions, the dominating factor (Ca-Dust) is enriched in both Ca and Mg, and is most probably emitted from regional sources. Its contribution to the atmospheric aerosol loading usually lies between 0.75 and 6.37μg/m 3 (10th and 90 th percentiles, respectively) but can peak at 9.28μg/m 3 . The second factor, simply referred to as the Dust factor, corresponds to dust emitted by, and transported from, more distant desert sources. During the massive advection events, its contribution to the aerosol loading in Sfax can be above 100μg/m 3 . Finally, the outdoor deposits of the residues of the local phosphate industry are an occasional source of P-enriched mineral dust (P-Dust) and some heavy metals (Cu, Ni, Zn, Pb). However, their contribution to the aerosol concentration is usually low (0.12–0.25μg/m 3 ) and does not seem to constitute an important source of contamination. Highlights: Apportioning the aerosol concentration in Central Tunisia. Mineral dust is the most variable component. Its composition is linked to that of the source-soil.